2018
DOI: 10.1063/1.5038912
|View full text |Cite
|
Sign up to set email alerts
|

Effective potential between negatively charged patches on acidic proteins immersed in various electrolyte solutions

Abstract: Effective interactions between O-sized anions in various electrolyte solutions were calculated by using the integral equation theory with some simple models. The results indicated that only multivalent cations mediated a strong effective attraction between O-sized anions at a certain concentration. The effective interaction turned from repulsive to attractive as the electrolyte concentration increased, and the effective attraction decreased when more electrolyte was added. Moreover, the effective interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Because the calculation cost for "Model A", that was mentioned above, was too expensive, the solvent hard spheres and the macroanions were removed from it. The results calculated using the HNC closure showed that the solvent hard spheres intensify the effective attraction between like-charged particles [40,41]. However, the explicit solvent model was not required, and the implicit solvent model also showed the effective attraction and the reentrant behavior in our studies [40,41].…”
Section: Model Bmentioning
confidence: 61%
See 3 more Smart Citations
“…Because the calculation cost for "Model A", that was mentioned above, was too expensive, the solvent hard spheres and the macroanions were removed from it. The results calculated using the HNC closure showed that the solvent hard spheres intensify the effective attraction between like-charged particles [40,41]. However, the explicit solvent model was not required, and the implicit solvent model also showed the effective attraction and the reentrant behavior in our studies [40,41].…”
Section: Model Bmentioning
confidence: 61%
“…The results calculated using the HNC closure showed that the solvent hard spheres intensify the effective attraction between like-charged particles [40,41]. However, the explicit solvent model was not required, and the implicit solvent model also showed the effective attraction and the reentrant behavior in our studies [40,41]. Therefore, this model was selected to reduce the computational costs.…”
Section: Model Bmentioning
confidence: 88%
See 2 more Smart Citations
“…His group mainly investigates effective intermolecular interactions in the liquid phase, phase behavior, and diffusion phenomena in a solution using statistical mechanics theory. For example, the group's theoretical studies for effective attraction between like-charged particles in an electrolyte solution explained the reentrant condensation behaviors of acidic protein (Akiyama and Sakata 2011;Suematsu et al 2018). The group is also studying various excluded volume effects in a liquid phase using Asakura-Oosawa theory and integral equation theory for liquids.…”
mentioning
confidence: 99%